Bidirectionally validated in silico and in vitro formation of specific depth zone-derived chondrocyte spheroids and clusters - Takada, Eiichiro; Mizuno, Hayato L.; Takeoka, Yoshiki; Mizuno, Shuichi (Frontiers in Bioengineering and Biotechnology, 2024)
3D multicellular self-organized cluster models e.g., organoids are promising tools for developing new therapeutic modalities including gene and cell therapies, pharmacological mechanistic and screening assays. Various applications of these models have been used extensively for decades, however, the mechanisms of cluster formation, maintenance, and degradation of these models are not even known over in-vitro-life-time. To explore such advantageous models mimicking native tissues or organs, it is necessary to understand aforementioned mechanisms. Wherein, we intend to clarify the mechanisms of the formation of cell clusters. We previously demonstrated that primary chondrocytes isolated from distinct longitudinal depth zones in articular cartilage formed zone-specific spherical multicellular clusters in vitro. To elucidate the mechanisms of such cluster formation, we simulated it using the computational Cellular Potts Model with parameters, which were translated from gene expression levels and histological characteristics corresponding interaction between cell and extracellular matrix. This simulation in silico was validated morphologically with cluster formation in vitro vice versa. Since zone specific chondrocyte cluster models in silico showed similarity with corresponding in vitro model, the in silico has a potential to be used for prediction of the 3D multicellular in vitro models used for development, disease, and therapeutic models.